2020
DOI: 10.7759/cureus.9415
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Fabry Disease Among Young Cryptogenic Stroke Patients

Abstract: Introduction Fabry disease is a metabolic storage disorder that causes disorders in multiple organs including the brain. Data regarding the prevalence of the disease among the Saudi stroke population is scarce. Hence, tests for the same are not conducted on a regular basis when investigating stroke of uncertain cause. Our study aimed to provide insight into whether testing for Fabry disease is justifiable in cryptogenic stroke patients who have no other features of the disease. Method This was a prospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Table 3 shows the bias of the studies included in this systematic review [1,2,[11][12][13][14][15][16]19].…”
Section: Study Limitationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 3 shows the bias of the studies included in this systematic review [1,2,[11][12][13][14][15][16]19].…”
Section: Study Limitationsmentioning
confidence: 99%
“…In five studies, the authors found that the sample was too small to reach statistical power [1,11,[14][15][16]. In the study by Kinoshita et al, genetic analysis was not conducted in each patient, which could lead to a measurement bias [14].…”
Section: Robins-i: Risk Of Bias In Non-randomized Studies Of Interventionsmentioning
confidence: 99%
See 3 more Smart Citations